Traffic Supervision by the Transportation Agency on Bukit Keminting Road, Palangka Raya - Nurul Nurul; Abdul Khair; Reza Noor Ihsan (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
Traffic supervision on Bukit Keminting Road, Jekan Raya District, is significant because the area is dense, contains busy intersections, and still shows violations despite the installation of traffic lights. Previous studies have mainly discussed governmental responsibility, general principles of good governance, or road safety in the abstract, leaving limited analysis of the Transportation Agency's supervision following the installation of traffic lights at a single local site. This study asks how the Transportation Agency implements supervision in line with good governance principles and which legal and non-legal obstacles necessitate administrative-law solutions. Data were processed through empirical legal research, involving interviews with the Transportation Agency, Traffic Police, students, and traders; field observations; accident documentation; and descriptive qualitative analysis using source triangulation. The findings show that the traffic light reduces vehicle speeds and the potential for accidents. However, supervision remains limited because red-light violations persist, signal timing is questioned, and night operations are inconsistent. The study concludes that the agency has applied prudence and utility, but needs monitoring, technical evaluation, police coordination, and public education.